Impact of Urea Fertiliser on Plant Tissue of Rice (Oryza sativa L) in Food Production - Anggita Ayu Faradiba; Emilia Yogi Dwi; , Ibrahim bin Sa’id (FAKULTAS PERTANIAN UNIVERSITAS RATU SAMBAN, 2023)
Indonesia is an agricultural country where the majority of its population lives in agriculture. Agriculture has a very important role in the national food security program. The issue of endangering national food security is a problem that must be faced by the Indonesian government. Increasing rice production is currently facing increasingly difficult challenges, both from a technical and non-technical perspective. There has also been an increase in the use of chemical fertilizers and pesticides to control nuisance organisms, which has a negative impact on environmental quality. In this article, the research method used is a qualitative descriptive analysis approach with a focus on library research and using technological assistance in the form of Artificial Intelligence in the form of Gpt Chat.